Identification and Prevention of Antiepileptic Drug Noncompliance: The Collaborative Use of State-Supplied Pharmaceutical Data. (19th February 2014) - Hodges, Joseph C.; Treadwell, Janet; Malphrus, Amy D.; Tran, Xuan G.; Giardino, Angelo P.
Abstract : Background . Antiepileptic drugs (AEDs) noncompliance is associated with increased risk of seizures and morbidity in seizure disorder patients. Objective . To identify risk factors that correlated to higher levels of morbidity, measured by emergency room (ER) utilization by seizure disorder members taking AED. Methods . Patients with primary or secondary diagnosis of seizures, convulsions, and/or epilepsy and prescribed AEDs during an 11-month period were included in the study. Variables were analyzed using multivariate statistical analysis including logistic regression. Results . The study identified 201 members. No statistical significance (NS) between age, gender, number of tablets, type of drug, or other risk factors was associated with increased mortality. Statistical significance resulted with medication compliance review of 0–14 days, 15–60 days, and 61+ days between refills. 68% of patients with ER visit had noncompliance refill between 0 and 14 days compared to 52% of patients in non-ER group (P = 0.04 ). Contrastingly, 15% of ER group had refills within 15–60 days compared with 33% of non-ER group (P = 0.01 ). There was NS difference between two groups when noncompliance was greater than 60 days (P = 0.66 ). Conclusions . The study suggests that careful monitoring of pharmaceutical refill information could be used to identify AED noncompliance in epileptic patients.